(untitled) (Research, Society and Development, 2020)
Objective: The objective of this study is to diagnose refractive errors in microcephaly’s children, presumably due to Zika virus congenital syndrome, in western Mato Grosso. Methods: Was performed an active search for patients with microcephaly treated at the Specialized Rehabilitation Center in Cáceres city, a reference in multiprofessional microcephally care in western Mato Grosso. Ophthalmological assessments were made of 30 children with microcephaly presumably due to congenital Zika virus syndrome, 14 males and 16 females with a mean age at the time of assessment of 2 years and 4 months. The children were referred to an ophthalmologist, where anamnesis was performed, a refractive examination by retinoscope equipament and schioscopy’s rules, using cyclopentolate eye drops. After the diagnosis of refractive errors, glasses were prescribed. Results: it was possible to diagnose refractive errors in 96,7% of the cases, the most found refractive error was astigmatism, diagnosed in 45 eyes, followed by hyperopia in 43 eyes and, finally, a myopia diagnosed in 12 eyes. Conclusion: The diagnosis of refractive errors was found in all 30 children, the absence of diagnosis and treatment can negatively affect the child development of this population; thus, early and continuous ophthalmological monitoring maximizes the visual quality and, consequently, the quality of life of patients and their families.